Partidos de esquerda no Brasil : desenvolvimento alternativo ou alternativas ao desenvolvimento? - Todt, Marcos Leite de Matos (2022)
Regarding the environmental theme, are there proposals based on strong sustainability in the government programs presented by the Brazilian left parties in the 2018 presidential elections? What is the existent space for post-developmentalist ideas and ideas based on strong sustainability in Brazil’s left parties? Based on these research questions, we analyzed the proposals by Brazilian left parties that presented their own candidacies in the 2018 presidential elections and interviewed environmental activists who are critical towards the developmentalism that is connected to these parties. We hypothesize that the Brazilian left is limited to thinking alternatives inside a developmental paradigm, based on the weak sustainability paradigm and, thus, the space for post-developmentalist ideas and such with strong sustainability is limited or inexistent. The evidence reveals that our hypothesis was proven right for the parties analyzed in this study, except partially for the Liberty and Socialism Party (PSOL). The interviewees who are affiliated to this party stated that PSOL has increasingly been more open regarding the eco-socialist and post-developmentalist agenda. Although the program presented by the party in 2018, in general, focuses on development; in the part concerning environment, there are proposals directly referred to in the international debate on alternatives to development and adherent to strong sustainability, which indicates that, in this party, strong sustainability has enough space to (at least) fight developmentalism for space.